Three-Dimensional Anisotropic Inversion for Controlled-Source Audio-Frequency Magnetotellurics Using Unstructured Tetrahedral Discretization - Ma, Fengqun; Tan, Handong; Zhu, Depeng; Riahi, Mohamed Kamel; Kong, Wenxin; Wang, Shuya (IEEE transactions on geoscience and remote sensing, 2025)
We propose a new 3-D arbitrary anisotropic inversion algorithm for controlled-source audio-frequency magnetotellurics (CSAMTs) with consideration of angle parameters. In this method, the study area is discretized using unstructured tetrahedral meshes, and vector basis functions are employed to interpolate electric and magnetic field values at the receiver locations. The anisotropic resistivity in the governing electromagnetic equations is described using a tensor, and parameterized by three principal resistivities and three Euler angles. The inversion problem is solved by the Limited-memory Broyden-Fletcher-Goldfarb-Shanno (L-BFGS) optimization scheme to efficiently find a reasonable model. We designed three representative types of synthetic models to investigate and test the algorithm: 1) anisotropic targets embedded in isotropic surrounding rocks; 2) isotropic targets surrounded by anisotropic media; and 3) complex models in which both targets and surrounding rocks exhibit anisotropy. The results demonstrate that the proposed inversion method can successfully recover these two horizontal principal resistivities, especially addressing the gap left by previous studies, as well as their corresponding rotation angles. For the second type of model, we further examined the influence of various initial models, particularly on the recovery of anisotropy angle parameters. Finally, by the separate inversion using the diagonal and off-diagonal components of the impedance tensor, we confirm the crucial role of off-diagonal components in the accurate reconstruction of the anomaly's shape and, especially, the angle parameters.